Age dependency and labour productivity divergence. Issue 50 (26th October 2016) - Choudhry, Misbah Tanveer; Marelli, Enrico; Signorelli, Marcello
ABSTRACT: This study finds strong empirical evidence in favour of the hypothesis that the age composition of population matters for labour productivity growth. We applied the fixed effects panel model using data on a large number of countries over the period 1980–2010. Our results suggest that higher age dependency not only directly impacts negatively on labour productivity but also modifies the impact of other determinants of labour productivity. Child dependency has a more adverse effect on labour productivity than old age dependency. We specifically find that the marginal effects of gross capital formation, information and communication improvement, and labour market reforms are significant at lower levels of age dependency. However, the marginal effect of savings on labour productivity is high at a high level of age dependency. The impact of age dependency varies between developed and developing economies. Diversity in the size and nature of age dependency across regions and different income groups help to explain the labour productivity differential across them.